Geomorphology of the northeast Sardinian continental shelf between Olbia and Posada (Italy) - M. De Luca; L. Casini; G. Cossu; G. De Falco; F. Gamberi; P. Marras; A. Santonastaso; M. Stelletti; V. Pascucci (Journal of Maps)
The Geomorphologycal map of the continental shelf of the northeaster sector of the Sardinian coast has allowed the recognition of several seafloor features. These have been related to the geology and climate history of the area from the Last Glacial Maximum (LGM) to the early Holocene. During the LGM sea level was about 130 below the present and cuspate deltas fed by rivers crossing the continental shelf formed. The post LGM sea level rise caused submersion of the exposed continental shelf and changed the dominant sedimentary processes. The rise was not continuous but punctuated by stillstands during which suites of beach ridges developed. The mapped ridges (BRS1, BRS2 and BRS3) are correlated to specific post-LGM sea level stillstands. These fit pretty well with the cold phases that punctuated the post LGM warming phase; that is, the Older Dryas (17-15 ka), Younger Dryas (12.9-11.6 ka) and the 8.2-kiloyear event (8.7-8.2 ka).